DAMPAK IMPLEMENTASI KURIKULUM MERDEKA TERHADAP KEMAMPUAN LITERASI SISWA DI SDN 3 JEROWARU :STUDI LITERATUR - Wiranti Nur Hidayah; Sri Sumartiningsih; Philip X. Fuchs (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low literacy skills of elementary school students and the importance of optimizing the implementation of the Kurikulum Merdeka to improve the quality of learning. Literacy encompasses not only reading and writing skills but also critical thinking and the ability to understand information contextually. This study aims to analyze the impact of the implementation of the Kurikulum Merdeka on students’ literacy skills at SDN 3 Jerowaru. The research method used is qualitative with a descriptive approach through a literature review, examining three relevant scientific journals. Data were collected through documentation techniques and analyzed using data reduction, data display, and conclusion drawing. The results indicate that the implementation of the Kurikulum Merdeka has a positive impact on improving students’ literacy skills, particularly in reading, writing, and critical thinking. Contextual, flexible, and project-based learning, along with the use of technology and the development of a literacy culture in schools, are key supporting factors. However, several challenges remain, including teacher readiness, limited facilities and infrastructure, and unequal access to learning resources. Therefore, appropriate strategies, improved teacher competencies, and adequate facilities are needed to optimize the implementation of the Kurikulum Merdeka in enhancing students’ literacy skills.